Feasibility and safety of the successive use of distal transradial access for coronary angiography and intervention in the same arm. Issue 6 (28th August 2021) - Yamada, Takeshi; Washimi, Soichiro; Hashimoto, Sho; Taniguchi, Norimasa; Nakajima, Shunsuke; Hata, Tetsuya; Takahashi, Akihiko
Abstract: Distal transradial access (dTRA) is a novel alternative to conventional radial artery access for coronary catheterization. However, the feasibility and safety of repeated use of dTRA have not been fully elucidated. This study aimed to evaluate the feasibility and safety of the repeated use of dTRA for coronary angiography and intervention in the same arm. A total of 1717 patients underwent angiography or angioplasty via dTRA. We retrospectively analyzed the catheterization records of patients who underwent repeated puncture of the distal radial artery in the same arm. The incidence of successive applications of dTRA and the reasons for dropout were retrospectively investigated. A total of 416 patients, including three who underwent coronary catheterization with the bilateral dTRA in the initial attempt were analyzed. A 3‐, 4‐, 5‐, or 6‐French sheath or sheathless guide catheter was used in the initial procedure. A maximum of four successive coronary catheterization procedures were performed. The second procedure with dTRA on the same arm was successfully performed in 395 cases (94.3%), with a successive rate of 89.6% for both the third and fourth dTRA procedures. Conversion to another approach site ( n = 30) was attributed to radial artery occlusion ( n = 9), narrowing of the distal radial artery ( n = 19), and puncture failure ( n = 2). The current data indicate that the repeated use of dTRA is safe and feasible, and this approach may become a standard approach site in the future.